Association Between Partial Pressure of Carbon Dioxide and Immediate Seizures in Patients With Primary Intracerebral Hemorrhage: A Propensity-Matched Analysis - Pan, Zhiming; Zhong, Qiuli; Wang, Chaoying; Wang, Jianqun; Chen, Xiaoyan; Li, Xiaoyan; Zhang, Xintong; Zhang, Yibin (Frontiers in Neurology, 2022)
Purpose To explore the value of partial pressure of carbon dioxide (PaCO2) levels in arterial blood for predicting immediate seizures (ISs) in patients with primary intracerebral hemorrhage (ICH). Methods Demographic information and clinical data from patients with primary ICH were prospectively collected, including arterial blood gas analysis. Immediate seizures (ISs) were determined as seizures in the first 24 h after admission. Univariate and multivariate analyses were performed to assess the association of PaCO2 levels with ISs. Propensity-score matching (PSM) analyses were adopted to reduce the baseline difference between ISs and non-ISs groups. Results A total of 596 patients with primary ICH were initially screened in this clinical study, 368 of whom fulfilled all the inclusion criteria [mean age, (60.46 ±12.78) years; 57.9% female patients]. ISs occurred in 30 of the 368 (8.15%) patients with primary ICH of this cohort. Patients with ISs had significantly lower PaCO2 levels [34.35(32.38–37.53) vs. 39.45(35.90–43.43), mmHg, p < 0.001] and were younger than those without ISs [(54.57±12.15 vs. 60.99 ±12.72) years, p = 0.008]. Multivariate analysis showed that lower initial PaCO2 (≤37.2 mmHg) level was a significant independent predictor of ISs [odds ratios (OR) 0.141, 95% confidence interval (CI) 0.057–0.351, p < 0.001], as well as younger age (OR 0.961, 95% CI 0.928–0.995, p = 0.023) and hematoma expansion (OR 0.340, 95% CI 0.134–0.863, p = 0.023). Receiver operating characteristic curve (ROC) analysis demonstrated that the optimal cutoff value of PaCO2 level for predicting ISs was 37.20 mmHg in patients with primary ICH (the area under the curve (AUC) was 0.760 with a corresponding sensitivity of 76.67% and specificity of 67.46%, 95%CI = 0.713–0.802, p < 0.001). After PSM, the matched ISs group had significantly lower PaCO2 levels compared with the matched non-ISs group [34.45(32.43–38.18) vs. 41.75(35.85–43.98) mmHg, p < 0.05] in the univariate analysis. The lower initial PaCO2 level was still independent of ISs following primary ICH. Conclusions The lower initial PaCO2 level was associated with an increased risk of ISs in patients with primary ICH.